Controllable preparation of helically structured polymer nanobelts by simple writing. (December 2019) - Han, Ying; Wang, Yunqiu; Jiang, Chunli; Lin, Hechun; Luo, Chunhua; Qi, Ruijuan; Huang, Rong; Peng, Hui
Graphical abstract: Different helical polymer nanobelts, including polypyrrole, PVP, PVDF-TrFE, PEG, PMVE-MA and PVA are prepared by using a simple direct writing technique. Highlights: Helical polypyrrole (PPy) nanobelts are prepared through a novel direct-writing method. Factors that affect the width and the shape of the nanobelts are investigated. The applicability and generality of this technique are illustrated by preparing helical nanobelts of different materials. The displacement sensor of PPy nanobelt and electric generator of PVDF-TrFE nanobelt are demonstrated. Abstract: A simple direct writing technique is developed for preparing helically structured nanobelts. The geometric asymmetry and surface strain contribute to the formation of helical structure. The shape of the helically structured nanobelts can be tuned by the nozzle size of micropipette and pulling speed. The applicability and generality of this technique are illustrated by successfully preparing the helical nanobelts of PPy, PVP, PVDF-TrFE, PEG, PMVE-MA and PVA. The potential applications of such helical structures in the area of sensor and energy harvesting are also demonstrated.